Sources of difficulty in learning the principles of Islamic jurisprudence (Usul Fiqh) among Islamic banking students of UiTM Machang - Zakaria, Razimi; Ismail, Mohd Saufi; Nik Hashim, Nik Ahmad Kamal Juhari; Tengku Abdul Aziz, YM Tengku Mohd Farid; Mohamed, Mohd Sollah (Universiti Teknologi MARA, Kelantan, 2018)
The research looks into the challenges of learning the Principles of Islamic Jurisprudence or Usul fiqh among UiTM Kelantan Islamic Banking students. Concerns have been voiced out by lecturers and students regarding the ability and performance to master the subject. Students faced a lot of difficulty in reading and explaining concepts in Islamic Jurisprudence and more than often their interpretations of the core concepts in Islamic Jurisprudence were erroneous. Previous semesters’ results had also shown an average performance among the students and a trend of 20% to 30% failures among the students taking the subject. The study obtained insights into sources of difficulty in learning the subject through classroom observations and interviews. It was found that the sources of difficulty in learning the subject expels around the areas of language proficiency and lack of background knowledge among the students. Bridging the gap between language issues and background knowledge is viewed as critical to ensure a more efficient learning of the subject as well as to solidify students’ understanding of the fundamental concepts in Usul fiqh.